Math, asked by akashjat915, 1 year ago

Simplify (x+y)³-(x-y)³-6y(x²-y²)

Answers

Answered by gravitation1
30
I hope you got the answer..
Attachments:
Answered by Anonymous
17

AnswEr:

We have,

\sf\red{(x+y)^3-(x-y)^3-6y(x^2-y^2)}

 \tt =  {(x + y)}^{3}  -  {(x - y)}^{3}  - 3 \times 2y \times (x + y)(x - y) \\  \\  \tt =  {[(x + y)}^{3}  -  {(x - y)]}^{3}  - 3(x + y) - (x - y) \\  \tt(x + y)(x - y) \\  \\  \tt =  {(x + y)}^{3}  -  {(x - y)}^{3} - 3(x + y)(x - y)[(x + y) - (x - y)] \\  \\  \tt =  {a}^{3}   -  {b}^{3}  - 3ab

_______________________________________

\sf\pink{Where\:a=x+y\:and\:b=x-y}

 \sf  =  {(a - b)}^{3}  = [(x + y) - (x - y)] {}^{3}  \\  \\  \sf \leadsto \:  {(2y)}^{3} = 8 {y}^{3}

#BAL

#Answerwithquality

Similar questions